Penyembelihan Wedhus Kendit di Tanggul Jebol Demak: Mitos, Perspektif Teologi dan Sosio-Kultural Masyarakat Jawa - Eny Junyanti; Ika Septiana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Traditional phenomena of the slaughter of wedhus kendit in Java, especially Norowito village, Karanganyar Prefecture, Demak Districk, Central Java, associated with the flood disaster that occurred in March 2024. Ritual in this respect is not just a cultural or religious practice, it encompasses complex mythological, theological, and socio-cultural aspects. The myths and beliefs about the wedhus of the frogs associate it with the Bathara Kala and the traditions of the earth, as well as preventing and protecting from catastrophe. Some people consider it a sacred habit, but others regard it as superstition or misleading. The majority of the inhabitants of the village of Norowito believe in this ritual, as evidenced by their participation in the slaughter ceremony and their belief that the wedhus will protect them from scourges. They also view this ritual as a way to find salvation in everyday life. The aim of this study is to understand the origins, significance, and influence of the tradition of wedhus slaughter, as well as its impact on the identity and life of the Java people. By studying further in these practices, it is expected to better understand the cultural wisdom and beliefs that make up this tradition, and the values held firmly by the local communities in daily life.